Carba-d, l-allal- and -d, l-galactal-derived vinyl N-nosyl aziridines as useful tools for the synthesis of 4-deoxy-4-(N-nosylamino)-2, 3-unsaturated-5a-carbasugars. Issue 48 (30th November 2017) - Di Bussolo, Valeria; Frau, Ileana; Favero, Lucilla; Bordoni, Vittorio; Crotti, Stefano; Uccello Barretta, Gloria; Balzano, Federica; Crotti, Paolo
Abstract: The novel carba-d, l -allal- and carba-d, l -galactal-derived vinyl N -nosyl aziridines were prepared and the regio- and stereoselective behavior in opening reactions with O - and N -nucleophiles examined. The carbaglycosylating ability of the novel aziridines, as deduced by the amount of 1, 4-addition products (1, 4-regioselectivity) obtained in the acid-catalyzed methanolysis taken as a model reaction, is similar or superior to that observed with the corresponding carba-d, l -allal- and -d, l -galactal-derived vinyl epoxides, respectively. In all 1, 2- and 1, 4-addition products obtained, a –( N -nosylamino) group is regio- and stereoselectively introduced at the C(4) carbon of a 1, 2- or 2, 3-unsaturated carbasugar, susceptible to further elaborations toward aminocyclitol derivatives. The stereoselective synthesis of the corresponding, enantiomerically pure carba-d, l -allal- and -d, l -galactal-derived vinyl N -acetyl aziridines is also described. Graphical abstract: